The international financial architecture and sustainable prosperity - Kevin Gallagher (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
The international financial architecture is misaligned with the goals set out in the UN Sustainable Development Goals and the Paris climate agreement. External financing flows to emerging-market and developing countries (excluding China) need be increasing by at least US1 trillion annually from 2030 onwards, but the highest level in the past decade was roughly one-third of what is necessary-with net inflows turning negative since 2021. Not only are the levels of capital too low: they are procyclical, destabilizing, have not been growth enhancing in general, and have not generated necessary structural transformation in particular. At exactly the moment when developing countries should be accelerating investment to meet these goals, the UN estimates that 3.3 billion people are living in countries that spend more on external debt service than on education or health. In addition to the international financial architecture's lack of ability to provide long-run, stable, and countercyclical finance to developing countries, it lacks an adequate 'global financial safety net' to prevent and mitigate increasing levels of external shocks including interest rate hikes, war and sanctions, and climate change. In response, developing nations resort to a mix of self-insuring reserve accumulation, private capital markets with unsustainable interest rates, and austerity-all of which further accentuate global imbalances, debt overhangs, and dim growth prospects. As part of broad reforms, multilateral development banks can play a central role in providing long-run, countercyclical finance to developing countries. Furthermore, the global financial safety net needs to be enlarged, deepened, and reoriented; and developing countries need to be a bigger part of the decisionmaking process within the international financial architecture. The costs of inaction on these matters far outweigh the relatively small effort that is urgently needed.
Keywords: O10; 019; Q56; 330; economic development; international organizations; environment; development